Radiocarbon and thermogravimetric analysis (TGA) results of leached permafrost from the Lena Delta, Arctic - Tsai-Wen Lin; Gernot Nehrke; Hendrik Grotheer; Boris P Koch; Gesine Mollenhauer (PANGAEA, 2025)
This datasheet includes radiocarbon and thermogravimetric analysis (TGA) results of the remaining permafrost after leaching from samples collected in the Lena Delta. The leaching protocol followed Ksionzek et al. (2018). Around 200 mg of dried sediment was leached in 20 mL deionized water for 24 hours at 4 °C, with intermittent shaking every 6-8 hours. After extracting the leachate, the remaining fraction was again freeze-dried. Pretreatment and measurement of radiocarbon analysis on the permafrost remainder followed Mollenhauer et al., 2021. Sediments were freeze-dried, ground, and weighed into silver boats, with sample sizes determined by TOC content to target 1 mg of organic carbon. Samples were acidified with three drops of 6 M HCl at 60 °C three times with one hour reaction time between treatments, then oven-dried overnight at 60 °C. Afterwards, acidified samples together with silver boats were folded into tin boats and converted into graphite targets using an elemental analyzer (Elementar vario Isotope) coupled to an automated graphitization system (Ionplus AG, AGE-3). Radiocarbon measurements were conducted using the MIni CArbon Dating System (MICADAS) accelerator mass spectrometer at Alfred Wegener Institute (AWI). For TGA analysis, about 20 mg of the remained permafrost were analyzed in 70 μL aluminum oxide crucibles using a Mettler Toledo TGA/DSC 1. The samples were heated from 25 to 1000 °C at a rate of 10 °C min-1 under a constant argon flow of 20 mL min-1, following similar settings from Smeaton & Austin (2022). Following Lopez-Capel et al. (2006), weight loss between 200–400 °C is attributed to the decomposition of labile organic matter (OML), while weight loss between 400–650°C corresponds to the decomposition of recalcitrant and refractory organic matter (OMR). The percentage of labile organic matter (OML/OM) is calculated as [OML/(OML+OMR)]*100%
In: Lin, Tsai-Wen; Nehrke, Gernot; Mollenhauer, Gesine (2025): Bulk organic matter data of Lena Delta permafrost, marine surface sediment, and sediment cores from the Laptev Sea, Arctic Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984732